MRC1 and LYVE1 expressing macrophages in vascular beds of GNAQ p.R183Q driven capillary malformations in Sturge Weber syndrome - Sana Nasim; Colette Bichsel; Stephen Dayneka; Robert Mannix; Annegret Holm; Mathew Vivero; Sanda Alexandrescu; Anna Pinto; Arin K. Greene; Donald E. Ingber; Joyce Bischoff (Acta Neuropathologica Communications, 2024)
Abstract Sturge-Weber syndrome (SWS), a neurocutaneous disorder, is characterized by capillary malformations (CM) in the skin, brain, and eyes. Patients may suffer from seizures, strokes, and glaucoma, and only symptomatic treatment is available. CM are comprised of enlarged vessels with endothelial cells (ECs) and disorganized mural cells. Our recent finding indicated that the R183Q mutation in ECs leads to heightened signaling through phospholipase Cβ3 and protein kinase C, leading to increased angiopoietin-2 (ANGPT2). Furthermore, knockdown of ANGPT2, a crucial mediator of pro-angiogenic signaling, inflammation, and vascular remodeling, in EC-R183Q rescued the enlarged vessel phenotype in vivo. This prompted us to look closer at the microenvironment in CM-affected vascular beds. We analyzed multiple brain histological sections from patients with GNAQ-R183Q CM and found enlarged vessels devoid of mural cells along with increased macrophage-like cells co-expressing MRC1 (CD206, a mannose receptor), CD163 (a scavenger receptor and marker of the monocyte/macrophage lineage), CD68 (a pan macrophage marker), and LYVE1 (a lymphatic marker expressed by some macrophages). These macrophages were not found in non-SWS control brain sections. To investigate the mechanism of increased macrophages in the perivascular environment, we examined THP1 (monocytic/macrophage cell line) cell adhesion to EC-R183Q versus EC-WT under static and laminar flow conditions. First, we observed increased THP1 cell adhesion to EC-R183Q compared to EC-WT under static conditions. Next, using live cell imaging, we found THP1 cell adhesion to EC-R183Q was dramatically increased under laminar flow conditions and could be inhibited by anti-ICAM1. ICAM1, an endothelial cell adhesion molecule required for leukocyte adhesion, was strongly expressed in the endothelium in SWS brain histological sections, suggesting a mechanism for recruitment of macrophages. In conclusion, our findings demonstrate that macrophages are an important component of the perivascular environment in CM suggesting they may contribute to the CM formation and SWS disease progression.